2012
DOI: 10.1007/s10336-012-0826-2
|View full text |Cite
|
Sign up to set email alerts
|

Dutch House Martins Delichon urbicum gain blood parasite infections over their lifetime, but do not seem to suffer

Abstract: In a southern Spanish population of the colonial-breeding Afrotropical migrant House Martins Delichon urbicum, a high overall prevalence of (molecularly assayed) haemosporidian infections (in the non-parasitological literature usually denoted with the inclusive term 'malaria') was associated with negative fitness consequences for individuals carrying single or double infections. To verify this in a northern population, we here report on the occurrence of malaria in 112 fledgling and 358 adult House Martins fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 24 publications
2
34
2
2
Order By: Relevance
“…Its main advantage is superior specificity, as it amplifies distinct avian malaria lineages. The effects of coexisting parasite lineages have drawn increasing interest (Valkiūnas et al 2003;Losieau et al 2010;Asghar et al 2011;Zehtindjiev et al 2011;Piersma and van der Velde 2012). Mixed infections might be expected to be especially severe (Graham et al 2005;Davidar and Morton 2006), hence the need for a protocol such as ours in future bird studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its main advantage is superior specificity, as it amplifies distinct avian malaria lineages. The effects of coexisting parasite lineages have drawn increasing interest (Valkiūnas et al 2003;Losieau et al 2010;Asghar et al 2011;Zehtindjiev et al 2011;Piersma and van der Velde 2012). Mixed infections might be expected to be especially severe (Graham et al 2005;Davidar and Morton 2006), hence the need for a protocol such as ours in future bird studies.…”
Section: Discussionmentioning
confidence: 99%
“…Coexisting parasites are often reported in birds (Valkiūnas et al 2003;Losieau et al 2010;Asghar et al 2011;Zehtindjiev et al 2011;Piersma and van der Velde 2012), but their effects are largely unknown. Some studies show aggravated effects of avian malaria co-infection (Marzal et al 2008) but others do not (Sanz et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…At the individual level Hasselquist et al [25] found that the likelihood of retaining the same infection status (infected vs. uninfected) for Haemoproteus payevskyi was higher than the probability of experiencing a change in status. Knowles et al [26] showed that 26% of Plasmodium infection in individual blue tits ( Cyanistes caeruleus ) from the UK could be lost over time, Piersma and van der Velde [27] found that 23% of house martins ( Delichon urbicum ) in the Netherlands showed no haemosporidian infection status changes over time and Latta and Ricklefs [28] found high individual turn-over in haemosporidian infections between years in various host species on the island of Hispaniola.…”
Section: Introductionmentioning
confidence: 99%
“…The 'heat dissipation limit (HDL) theory' (Speakman and Król, 2010) suggests that intake is constrained by the capacity to dissipate the heat generated as a by-product of food utilisation and milk production. Finally, a trade-off idea suggests that working beyond a certain limit generates negative physiological consequences that impact survival (Drent and Daan, 1980;Daan et al, 1996;Piersma, 2011;Piersma and van der Velde, 2012). The HDL theory could be considered a special case of this latter idea, because the implication is that processing food and elevating metabolic rate beyond the heat dissipation capacity leads to hyperthermia, with direct or indirect negative consequences for survival.…”
Section: Introductionmentioning
confidence: 99%